The Parable of the Good Shepherd in Contemporary Life in the Gospel of John 10 verses 1-21 - Sarmauli; Alpida, Alpida; Dandi, Dandi; DanielNP., DanielNP. (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This study examines the application of the parable of the Good Shepherd in contemporary life, focusing on the aspects of spiritual leadership, protection and sacrifice, recognition and obedience, rejection and acceptance, and resurrection and eternal life. Through literature analysis, this study identifies how the concept of the Good Shepherd in John 10:1-21 can be implemented in the daily lives of Christians. Jesus is portrayed as the Good Shepherd, who leads, protects and sacrifices Himself for His sheep. Spiritual leaders in modern times can take this example to guide and serve the congregation with genuine love and sacrifice. This study highlights the importance of knowing and obeying the voice of Jesus, discerning between truth and deception, and living in awareness of the promise of resurrection and eternal life. The results show that this parable remains relevant and provides meaningful guidance for the spiritual and practical lives of Christians.